Analisis Kelayakan Usaha Pedagang Sagu di Pasar Wamanggu dan Pasar Mopah Baru Distrik Merauke Kabupaten Merauke - Longan, Isak; Widyantari, Ineke Nursih; Untari, Untari (Musamus University, 2023)
The purpose of determine how much the costs incurred, sago traders, how much profit the sago traders get, how the business feasibility of sago traders is. at Wamanggu Market and Mopah Brau Market in Merauke District, Merauke Regency. location determination is done intentionally. The population in this study were all sago traders in Wamanggu Market and Mopah Baru Market as many as 32 respondents. The sample determination in this study was by census. The data used were primary data which included observation and interviews. While secondary data were journals and literature. The data analysis technique uses the income formula and R/C Ratio. The results of this study were the income of sago traders in Wamanggu Market and Mopah Baru Market was Rp.464,252 the profit obtained was Rp.1,807,002 with an R/C Ratio of 1.95 den of 1.93. This means that the business of sago traders in Wamanggu Market and the New Mopah Market in the Merauke District, Merauke Regency, which is worth trying.